The complete chloroplast genome sequence of Knema furfuracea (Myristicaceae) - Tian Yang; Chang-Li Mao; Xiao-Qin Li; Feng-Liang Zhang; Qi Zhao; Yu Wu (Mitochondrial DNA. Part B. Resources, 2020)
Knema furfuracea is a member of Myristicaceae. The K. furfuracea chloroplast genome is found to be 154,527 bp in length and has a base composition of A (29.99%), G (19.31%), C (19.92%), and T (30.78%). The genome contained two short inverted repeat (IRa and IRb) regions (48,110 bp) which were separated by a large single copy (LSC) region (86,188 bp) and a small single copy (SSC) region (20,229 bp). The chloroplast genome has 87 protein-coding genes, 27 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. Further, complete chloroplast sequence of K. furfuracea was aligned together with two species of Myristicaceae and five basal angiosperms species which have reported the complete chloroplast sequence. This complete chloroplast genome will provide valuable information for the development of DNA markers for future species resource development and phylogenetic analysis of K. furfuracea.